AKIBAT: Game Horor Perdukunan Berbasis Mobile - Muhammad Ichsan Nurfauzi; Amir Hasanudin Fauzi; Rivaldo Eduard Renyaan (Journal of Applied Engineering and Social Science (JAESS), 2024)
The author aims to create a horror game in Indonesian language called ”Akibat” that intends to raise awareness amongsociety about the consequences of seeking instant gratification through mysticism, either for personal gain or hurting others.In ”Akibat,” players will encounter different stories and mechanics that require unique solutions to complete each narrative.”Akibat” is an Android game targeted at the teenage market with a minimum age rating of 12 years and above. The gamehas been rated T for Teen by ESRB and PEGI 12 by PEGI, with minimal violence and blood. Its purpose is to serve as abridge for teenagers to gradually explore more mature content involving violence and battles. Moreover, ”Akibat” is expectedto serve as an engaging medium to introduce Indonesian culture, particularly to teenagers, helping them better understandthe horror and mysticism elements embedded in Indonesian life. User testing with 20 respondents revealed that 83.7% ofthem acknowledged the game’s success in introducing Indonesia’s rich culture, encompassing urban legends and horrortales involving agreements with mystical figures. Users agreed that ”Akibat” serves as an excellent means to introduceculture to individuals aged 12 and above